Takotsubo syndrome: state-of-the-art review by an expert panel - part 2 - Dias, Andre; Núñez Gil, Ivan J.; Santoro, Francesco; Madias, John E.; Pelliccia, Francesco; Brunetti, Natale Daniele; Salmoirago-Blotcher, Elena; Sharkey, Scott W.; Eitel, Ingo; Akashi, Yoshihiro J.; El-Battrawy, Ibrahim; Franco, Emiliana; et al. (Cardiovascular revascularization medicine, 2019)
Takotsubo syndrome (TTS) is an acute cardiac condition independent of epicardial coronary obstruction that mimics acute coronary syndrome and is characterized by acute heart failure with reversible ventricular motion abnormalities. This consensus paper is the result of a multinational effort aiming to summarize the current state of the art on TTS. Experts in the field provide a thorough and detailed review of this syndrome. Several novel and unique sections are emphasized in this document, including the current state of the art on genetics of takotsubo syndrome, microRNAs (miRs), racial differences, role of cardiac spectroscopy and intracoronary imaging, as well as mechanical circulatory support. In part 1 of this two-part manuscript, we discuss how TTS came to be known, several patterns and forms it can take in patients, epidemiology and pathophysiology of the syndrome, and clinical presentation.